Guest

Solve this: 1.tantheta / 1-tan square theta = sintheta sin (90-theta) / 2sinsquare (90-theta)-1 2. 1 / (cosec theta – cot theta) – 1 / sintheta = 1/sintheta – 1/(cosec theta+cottheta) 3.(cotsquare theta + secsquare theta) / (tansquare theta + cosec square theta) = (sintheta costheta) (tan theta + cot theta)

Solve this:
1.tantheta / 1-tan square theta  =                        sintheta sin (90-theta)  / 2sinsquare (90-theta)-1
 
2. 1 / (cosec theta – cot theta)    – 1 / sintheta   =  1/sintheta  –  1/(cosec theta+cottheta)
 
3.(cotsquare theta + secsquare theta) / (tansquare theta + cosec square theta)  =  (sintheta costheta) (tan theta + cot theta)

Grade:12th pass

1 Answers

Drishtant Mishra
13 Points
5 years ago
And 1=LHSReplacing theta by "x" for ease in typing tanx/1-tan^2x=sinx/cosx/1-sin^2x/cos^2sinx/cosx/cos^2-sin^2x/cos^2Sinx.cosx/cos2x =LHS (Since cos^2-sin^2x=cos2x) RHSsinx.sin(90-x)/2sin^2 (90-x)-1sinx.cosx/2cos^2x-1 =RHShence RHS=LHSsinx.cosx/cos2x

Think You Can Provide A Better Answer ?